Extraction and Characterization of Silicon Dioxide from Coal Fly Ash as Counter Electrode Material in Dye-Sensitized Solar Cells (DSSCs) - Mitha Pratiwi; Leila Kalsum; Rusdianasari Rusdianasari (Jurnal Kimia Sains dan Aplikasi, 2024)
The counter electrode in DSSCs must be made of a material with various advantageous chemical and physical characteristics to guarantee the cell’s efficient functioning and cost efficiency. Coal fly ash is recognized for its substantial silicon dioxide (SiO2) content and other minerals and metals. This paper provides a detailed analysis and description of extracting and characterizing SiO2 from coal fly ash. This extraction aims to utilize SiO2 as a material for the counter electrode in DSSCs. The extraction procedure of SiO2 from coal fly ash involves a multi-step process that entailed the utilization of acid leaching using hydrochloric acid 1 M at 90°C for 4 h, which was subsequently followed by precipitation using NaOH 3 M at 90°C for 4 h to separate SiO2. The SiO2 gel was cleaned of contaminants with hot distilled water and dried at 110°C for 12 h. The SiO2 that was obtained was analyzed utilizing a range of analytical techniques to evaluate its structural, morphological, chemical, and optical properties. The X-ray diffractometer (XRD) examination revealed that the crystal structure of coal fly ash consisted of quartz, corundum, hematite, lime, and periclase. The SiO2 that was obtained exhibited a crystal structure that was both cubic and triclinic. The morphology is visualized using a scanning electron microscope (SEM). The study using atomic absorption spectroscopy revealed that the coal fly ash contained 52.91% SiO2, whereas the extracted SiO2 had a purity of 91.20%. The UV-Vis spectrophotometry investigation revealed that the SiO2 exhibited absorbance spectra with a wide band gap of 4.17 eV, whereas the coal fly ash had absorbance spectra of 3.37 eV.